Metaphor, Language, and Thinking Time: Rejuvenating Northrop Frye's Concept of Metaphor Via Gustave Guillaume's Thinking Time - Howlett, Carson (My University, 2007)
This thesis is an experiment in using Northrop Frye's concept of metaphor, as articulated in The Great Code, Words With Power, and On Religion, to illuminate how the habit of language can remind us that our cultural paradigms are always created and we have the ability to think above them. The thesis will begin by explaining how Frye utilises Giambattista Vicos' ideas of "Verum Factum" and the ''three stages of history" to formulate his ideas on metaphor. It will then be argued that Gustave Guillaume's ideas on language, in particular "thinking time," can illuminate for the reader a new concept of how thinking about language can remind us of our creative imagination. The part of imaginative thinking that Frye refers to as "ecstatic metaphor." Finally, Samuel Butler's book Life and Habit will be utilised to demonstrate that with practice, and the proper thoughts on language, one can consistently think beyond that which has been created for them.
Keywords: Religion; Religion